Metode Pembelajaran PAI Mengatasi Kesulitan Siswa Membaca Iqra’ di Kelas 1 SDIT Baiturrahim Parik Putuih Agam - Febriani, Wilda; Hariga, Srabu; M, Iswantir (Lembaga Yasin AlSys, 2023)
Learning to read Iqra' which is held at SDIT Baiturrahim Parik Putuih It is a routine activity that is carried out every morning after the Dhuha prayer, Iqra' learning is carried out before carrying out the teaching and learning process, namely at 08.30 WIB, reading the Koran is carried out for 30 minutes. The formulation of the problem in this study includes the following: 1). What is the method of Islamic Religious Education in overcoming reading difficulties for iqra' grade 1 students at SDIT Baiturrahim Parik Putuih. 2). What methods are used by Islamic religious education teachers in overcoming Iqra reading difficulties for grade 1 students at SDIT Baiturrahim Parik Putuih. This study uses a type of qualitative research, data collection techniques that the authors apply in the preparation of this article, namely observation and interviews. The results of this study indicate that: 1). the method of Islamic religious education in overcoming students' difficulties in reading iqra' by using the iqro method (reading the letters of the Koran fluently) and this method does not require various tools because it is only aimed at reading it. .2) What methods do Islamic Religious Education teachers use in overcoming Iqra' reading difficulties, namely using individual, individual or individual teaching? Individuals advance one by one to the teacher according to each page. parents to encourage their children to continue learning to read Iqra' at home so that their children are fluent in reading Iqra' at school.